Extremal problems of nonoverlapping domains with free poles on a circle - Bakhtin, A. K. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
Let $α_1, α_2 > 0$ and let $r(B, a)$ be the interior radius of the domain $B$ lying in the extended complex plane $\overline{ℂ}$ relative to the point $a ∈ B$. In terms of quadratic differentials, we give a complete description of extremal configurations in the problem of maximization of the functional $\left( {\frac{{r(B_1 ,a_1 ) r(B_3 ,a_3 )}}{{\left| {a_1 - a_3 } \right|^2 }}} \right)^{α _1 } \left( {\frac{{r(B_2 ,a_2 ) r(B_4 ,a_4 )}}{{\left| {a_2 - a_4 } \right|^2 }}} \right)^{α _2 }$ defined on all collections consisting of points $a_1, a_2, a_3, a_4 ∈ \{z ∈ ℂ: |z| = 1\}$ and pairwise-disjoint domains $B_1, B_2, B_3, B_4 ⊂ \overline{ℂ}$such that $a_1 ∈ B_1, a_1 ∈ B_2, a_3 ∈ B_3, and a_4 ∈ B_4$.